INTERNATIONAL EXPERIENCE IN INTERIOR DESIGN AND EQUIPMENT OF TEMPORARY HOUSING FOR INTERNALLY DISPLACED PERSONS - Шмельова-Нестеренко , Олександра Євгеніївна; Косенко, Данило Юрійович; Ганущак-Єфіменко, Людмила Михайлівна; Агліуллін, Руслан Марселєвич; Вишневська, Олена Вячеславівна; Закутенко, Вікторія Леонідівна (Art and Design, 2023)
The purpose of the study is to analyze the global experience in designing temporary housing for Internally Displaced Persons (IDPs). Methodology of the research involves a comprehensive study of the article's theme, utilizing general scientific methods such as analysis, systematization, generalization, and comparison. The empirical basis for the scientific work includes scientific publications and articles, as well as implemented experience in designing temporary housing for IDPs in Ukraine and abroad. The paper presents the results of analyzing contemporary trends in designing temporary housing for IDPs. The foreign and Ukrainian experiences in designing various types of housing for internally displaced persons have been systematized. It has been determined that in EU countries, three approaches are applied to provide housing for IDPs: resettlement of IDPs in social housing, temporary modular housing, and non-residential premises (where temporary living conditions are created or reconstruction is carried out). Basic features of organizing temporary housing for IDPs have been identified, and the main principles of designing such housing aimed at improving the residents' quality of life and their psychological and physical comfort have been formulated. The global experience in designing various types of housing for internally displaced persons has been analyzed and systematized, with the main parameters characteristic of each type of housing identified. The conducted research, aimed at identifying the peculiarities of designing temporary housing for IDPs, can be utilized by architects and interior designers in the design of such housing.